Acupoint application improves IVF outcomes and rescues granulosa cell steroid metabolic dysregulation in ovarian endometriosis - Ai, Kai-Liang; Cao, Xian-Ling; Gao, Yu-Qi; Cao, Jing-Xian; Sun, Zhen-Gao (Frontiers in Endocrinology, 2025)
Background and objectiveOvarian endometriosis (OE), characterized by endometriotic cysts, adversely affects ovarian function and comprises in vitro fertilization and embryo transfer (IVF-ET) outcomes. Acupoint application therapy (AAT), which integrates transdermal drug delivery with acupoint stimulation, may offer therapeutic benefits; however, its underlying mechanisms remain unclear.MethodsIn this randomized trial, 81 IVF-ET patients were stratified into: a treatment group comprising OE patients (n=27) undergoing a gonadotropin hormone-releasing hormone (GnRH) antagonist protocol with medicated AAT, a placebo group consisting of OE patients (n=26) following an identical protocol but receiving a sham patch, and a control group, including patients with male-factor infertility (n=28) undergoing the standard protocol without additional interventions. Follicular fluid metabolomics (assessed by Ultra High-Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS/MS) System)and IVF parameters were analyzed.ResultsSignificant intergroup differences were observed (one-way ANOVA, P < 0.05). The treatment group exhibited a shorter Gn duration (9.00 ± 0.68 days) compared to the placebo group (10.62 ± 2.43 days; P < 0.05), with a duration comparable to the male-factor control group (9.32 ± 1.89 days; NS). Similarly, the total Gn dose was lower in the treatment group (2112.50 ± 483.17 IU) than in the placebo group (2549.04 ± 677.44 IU; P < 0.05), and comparable to the control group (2105.89 ± 690.24 IU; NS). Regarding IVF outcomes, the treatment group yielded more oocytes retrieved (12.41 ± 7.27) than the placebo group (8.85 ± 7.89; P < 0.05), though fewer than the control group (15.25 ± 7.77). Fertilized oocytes were also higher in the treatment group (7.59 ± 4.58) compared to the placebo group (4.46 ± 3.40; P < 0.05), but fewer than in the control group (9.21 ± 4.82). The number of transferable embryos was comparable between the treatment group (3.33 ± 2.30) and the control group (3.43 ± 2.13; NS), and significantly higher than in the placebo group (1.69 ± 1.87; P < 0.05). Furthermore, the treatment group produced more high-quality embryos (3.04 ± 1.89) than the placebo group (1.35 ± 1.99; P < 0.05), and more than the control group (2.43 ± 1.95). No significant intergroup difference was found in fertilization rates (64.40% vs. 62.90% vs. 60.90%; NS). However, the high-quality embryo rate was significantly higher in the treatment group (47.02%) compared to both the placebo (31.15%; P < 0.05) and control (29.05%; P < 0.05) groups. Finally, the treatment group demonstrated a significantly greater reduction in peri-menstrual abdominal pain scores (Δ=−1.15 ± 0.36) compared to the placebo group (Δ=−0.35 ± 0.49; F = 6.84, P = 0.01). Metabolomic analysis revealed that the steroid hormone biosynthesis pathway was the most significantly disturbed in OE patients, characterized by markedly elevated levels of key intermediates such as 17α-hydroxyprogesterne. Critically, the levels of 17α-hydroxyprogesterone exhibited a significant negative correlation with oocyte yield (r = -0.286, p = 0.012), directly linking this metabolic dysregulation to impaired clinical outcome. Furthermore, oxidative stress metabolites showed a strong positive correlation with the luteinization marker 20α-hydroxy-4-pregnen-3-one (r = 0.43, p = 0.001), suggesting a potential interaction between oxidative stress and aberrant steroidogenesis. The AAT intervention effectively normalized this dysregulated steroidogenic profile, which underpinned the observed therapeutic benefits.ConclusionAAT significantly alleviates peri-menstrual pain and enhances IVF outcomes in ovarian endometriosis patients, which may be attributed to the restoration of granulosa cell steroid metabolism, evidenced by normalized levels of 17α-hydroxyprogesterone and attenuation of oxidative stress.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2200057339.